Algebraic dependences of meromorphic mappings in several complex variables - Pham, Duc Thoan; Pham, Viet Duc (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We give some theorems on algebraic dependence of meromorphic mappings in several complex variables into complex projective spaces.